Comparison of the Appendicitis Inflammatory Response System and Alvarado Scores for the Prediction of the Acute Appendicitis - Ibn E Ali, Paras; Malhi, Muhammad Ayub Ashraf; Abbas, Nosheen; Muhammad, Ammara Iqbal; Ali, Usman Bin; Ashraf , Sohaib (Pakistan Armed Forces Medical Journal, 2024)
Objective: To evaluate the accuracy of Appendicitis Inflammatory Response system in comparison to that of the Alvarado score for the diagnosis of the acute appendicitis. Study Design: Validation study. Place and Duration of Study: Accident and Emergency Department of Combined Military Hospital Rawalpindi, Pakistan, from Aug 2021 to Jan 2022. Methodology: A total of 150 patients who presented to accident and emergency department with complaints of pain in right iliac fossa and were diagnosed clinically by surgeons as cases of acute appendicitis were included. Appendicitis Inflammatory Response and Alvarado scores were calculated for all patients and diagnostic accuracy was compared for both scores taking the histopathology report as the gold standard. Results: The study had 87(56.1%) males and 63(40.6%) females. Ninety-six (61.9%) individuals were below 40 years of age. Ninety-nine (63.9%) of the patients presented within 48 hours of onset of symptoms. The sensitivity, specificity, PPV, NPV and accuracy were calculated as 89.4%, 77.8%, 50%, 96.7% and 88% for Appendicitis Inflammatory Response scoring system and 74.2%, 77.8%, 29.2%, 96.1% and 74.6% for Alvarado score respectively. Conclusion: The diagnostic accuracy of Appendicitis Inflammatory Response score was better as compared to Alvarado in diagnosis of acute appendicitis.